2011
DOI: 10.1007/s12529-011-9156-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support, Coping Styles, and Chinese Immigrants’ Cardiovascular Responses to Stress

Abstract: Background Social support and coping strategies are important determinants of health, especially for those in the immigrant community adjusting to a new environment. Purpose This study assessed the buffering effects of perceived social support and different coping styles on cardiovascular reactivity to stress among Chinese immigrants in the New York City Chinatown area. Method Participants (N = 50, 76% women, and 22–84 years old) completed questionnaires assessing their perceived social support and coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 55 publications
1
35
1
1
Order By: Relevance
“…In an interesting study that examined marital satisfaction of Chinese under stress, an incidental finding showed that social support was a key factor in reducing the negative effects of life crises (Chi et al, 2011). Lee, Suchday and Wylie-Rosett (2012) stated that with the perception of a strong social support network, an individual was better able to cope with adverse situations, relative to someone who had to cope alone.…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting study that examined marital satisfaction of Chinese under stress, an incidental finding showed that social support was a key factor in reducing the negative effects of life crises (Chi et al, 2011). Lee, Suchday and Wylie-Rosett (2012) stated that with the perception of a strong social support network, an individual was better able to cope with adverse situations, relative to someone who had to cope alone.…”
Section: Discussionmentioning
confidence: 99%
“…Coping styles reflect both strategies used to cope with various stressors and people's habitual preferences in coping with problems [39]. In this study, we evaluated the associations between three dimensions of coping (i.e., problem focused, emotion focused, and nonfunctional) with Internet addiction by controlling for the effect of depression in college students.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Research found that depressive symptoms and depressive disorders are prevalent among those who used to cope with stress by denial [39]. Meanwhile, depression was significantly associated with Internet addiction [9].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many receive help with living arrangements, daily needs, or finding jobs from family friends, relatives, or people from the same hometown. Research has found that in Chinese immigrant communities, greater upholding of Chinese values was positively associated with stronger perceived availability of social support in time of need (Lee, Suchday, & Wylie-Rosett, 2012). Chinese also tend to remain connected with family and friends from the home country after immigration, as immigration is usually seen as family pride that enhances the social status of the family in the guanxi network, in both the home country and the host country (Lai et al, 2012).…”
Section: Guanxi In Immigrant Communitiesmentioning
confidence: 99%